Regionally restricted modulation of Sam68 expression and Arhgef9 alternative splicing in the hippocampus of a murine model of multiple sclerosis - Adinolfi, Annalisa; Di Sante, Gabriele; Rivignani Vaccari, Luca; Tredicine, Maria; Ria, Francesco; Bonvissuto, Davide; Corvino, Valentina; Sette, Claudio; Geloso, Maria Concetta (Frontiers in Molecular Neuroscience, 2023)
Multiple sclerosis (MS) and its preclinical models are characterized by marked changes in neuroplasticity, including excitatory/inhibitory imbalance and synaptic dysfunction that are believed to underlie the progressive cognitive impairment (CI), which represents a significant clinical hallmark of the disease. In this study, we investigated several parameters of neuroplasticity in the hippocampus of the experimental autoimmune encephalomyelitis (EAE) SJL/J mouse model, characterized by rostral inflammatory and demyelinating lesions similar to Relapsing-Remitting MS. By combining morphological and molecular analyses, we found that the hippocampus undergoes extensive inflammation in EAE-mice, more pronounced in the CA3 and dentate gyrus (DG) subfields than in theCA1, associated with changes in GABAergic circuitry, as indicated by the increased expression of the interneuron-marker Parvalbumin selectively in CA3. By laser-microdissection, we investigated the impact of EAE on the alternative splicing of Arhgef9, a gene encoding a post-synaptic protein playing an essential role in GABAergic synapses and whose mutations have been related to CI and epilepsy. Our results indicate that EAE induces a specific increase in inclusion of the alternative exon 11a only in the CA3 and DG subfields, in line with the higher local levels of inflammation. Consistently, we found a region-specific downregulation of Sam68, a splicing-factor that represses this splicing event. Collectively, our findings confirm a regionalized distribution of inflammation in the hippocampus of EAE-mice. Moreover, since neuronal circuit rearrangement and dynamic remodelling of structural components of the synapse are key processes that contribute to neuroplasticity, our study suggests potential new molecular players involved in EAE-induced hippocampal dysfunction.